2015
DOI: 10.1080/19443994.2013.860625
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of uranium by low-cost adsorbent derived from agricultural wastes in multi-component system

Abstract: A B S T R A C TThe impact of common cations and anions on the adsorption of uranium on rice straw activated carbon has been examined. The presence of these ions in solution was found to inhibit the uptake of cadmium by chitin to different degrees. Presence of Fe ions depressed the uranium removal to 77 and 20% at 20 and 100 mg/l, respectively. Coexistence of some anions induced small positive effect on uranium adsorption percent like Cl -; 91.0%, CO 2À 3 ; 89.3%, HCO À 3 ; 88.8%, S 2 O 2À 3 ; 93.8%, and OH -; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This is good for our carbon as it was reported that the carbon mesopores enhanced its adsorption capacity for metals [18]. The full details of single-component adsorption of uranium and thorium on activated carbons RSK and RSN were described in our previous work [11]. In this concern, RSK was determined to be superior in removal of uranium while RSN for thorium than nonoxidized carbon.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…This is good for our carbon as it was reported that the carbon mesopores enhanced its adsorption capacity for metals [18]. The full details of single-component adsorption of uranium and thorium on activated carbons RSK and RSN were described in our previous work [11]. In this concern, RSK was determined to be superior in removal of uranium while RSN for thorium than nonoxidized carbon.…”
Section: Resultsmentioning
confidence: 79%
“…RSK has low value of acidic groups, such as carboxyl, hydroxyl, and carbonyl [11] to which alkali ions can attach so that alkali metal ion didnot adsorb and didnot affect the uranium adsorption. The minor effect of light metals on the adsorption of uranium onto RSK indicates the selectivity of the uptake of uranium onto this carbon.…”
Section: It Is Obvious Frommentioning
confidence: 99%
See 2 more Smart Citations
“…Like many other heavy metals such as chromium, lead, mercury and nickel, uranium and its compounds are highly poisonous substances. Uranium can enter the human body through respiration or through contact with an open wounds and its radioactivity also poses increased risks of lung cancer and bone cancer [1][2][3][4]. Thus, removal of uranyl ions from wastewater should be concerned because of the significance of potential environmental hazards.…”
Section: Introductionmentioning
confidence: 98%